Microbiota and Dysbiosis of the Human Digestive Tract - Health Consequences - Khetsuriani, Shorena (Microbiota and Dysbiosis of the Human Digestive Tract - Health Consequences, 2023)
The book covers key aspects of the role and functioning of human digestive tract microbiota and various mechanisms and clinical outcomes of dysbiotic changes are also discussed. There are presented microbial diversity, characteristics of the composition of different sites of the digestive tract, and their strong involvement and influence in health conditions. There are provided recent findings of microbial metabolites, mechanisms of immune and inflammatory responses, and bacterial-drug interactions. Where applicable, mechanism-based discussions are represented also. The materials are suitable for students, health professionals, researchers, and interested readers in the field of medical and biomedical sciences.